The Impact of Climate Change on the Geopolitics of the Arctic Circle - Turnham, James (Univerzita Karlova, Fakulta sociálních věd, 2022)
At the top of the world, worn like a crown, lies the Arctic. For much of human history it has been home to only a few hardy souls, eking out an existence in a cold unforgiving land. However, as the ages have marched by, man has attempted to explore and exploit the region as despite the Arctic's hostility, it contains a vast array of wealth. However, despite the richness of the land, remarkably little geopolitical competition has occurred above the Arctic Circle. The vast proportion of scholars and observers in the modern era have viewed the Arctic as a place where, perhaps uniquely, the quintessential regime of security dilemmas and competition between great powers, portrayed by realist scholars, has failed to manifest itself. However, as climate change wracks the region, seeing temperatures soar, the permafrost thaw, and the sea-ice rapidly becoming no more, the Arctic has reached a critical juncture where both the technology and the climate allow for an expanding human presence in the Arctic Circle and the economically viable exploitation of its wealth. This paper seeks to discover the impact of these drastic changes on the great power politics and potential future securitisation of the region. Katedra politologie Department of Political Science Faculty of Social Sciences Fakulta sociálních věd